An Improved NGS Library Construction Approach Using DNA Isolated from Human Cancer Formalin‐Fixed Paraffin‐Embedded Samples. Issue 6 (25th November 2018) - Zhang, Chunze; Wang, Yijia; Hu, Xia; Qin, Litao; Yin, Tingting; Fu, Wenzheng; Fan, Guanwei; Zhang, Heng; Liu, Guang; Jiang, Zhi; Zhang, Xipeng; Li, Xichuan
ABSTRACT: Identification of genomic alterations from formalin‐fixed paraffin‐embedded (FFPE) samples using next‐generation sequencing (NGS) is very important for cancer‐targeted therapy today. To achieve a higher efficiency and shorter turn‐around time for NGS library preparation, here, we compared NGS library preparation processes and outcomes with three commercial library construction methods and two hybridization capture methods thus, developed an improved NGS library construction approach. This improved approach took advantage of both methods and resulted in a higher output from the same input DNA, including higher library construction success rate, higher probe capture rate, and shorter turn‐around time. Using this approach, targeted region libraries could be constructed within only 1 day for FFPE samples; therefore, this approach has potential applications of NGS in routine clinical tests. Anat Rec, 302:941–946, 2019. © 2018 Wiley Periodicals, Inc.